Sosialisasi Penerapan Tanda Waqaf Dalam Al-Qur’an Rasm Utsmani Di Kecamatan Tajur Halang - Fajar Erlangga; Fery Rahmawan Asma; Muhammad Soleh Ritonga; Nur Ali (CV. Multi Kreasi Media, 2025)
Most Muslims often make mistakes in applying waqaf signs in Al-Qur'an, resulting in an inability to maintain the correct flow and meaning of the text during recitation. Therefore, the aim of this Community Service (Abdimas) is to enhance community understanding and awareness in correctly applying waqaf signs in Al-Qur'an, particularly the one in Uthmani rasm. The method employed in the Abdimas was lecture-based method, involving direct interaction with the local community, specifically the congregation of Musholla Al-Jihad in Tajur Halang District. This method was supported by some stages including pre-preparation, planning, execution, and evaluation. The results demonstrated a significant improvement in understanding and positive responses from the congregation towards the structured learning modules. This program has not only succeeded in improving Qur'anic reading skills but also in fostering awareness of the importance of Tajwid literacy and waqaf signs among Muslims. The implication of this dissemination include serving as a model for similar programs that can strengthen the relationship between Abdimas activities and the community, enhancing the quality of their religious life in the future.